The Association of Left Atrial Appendage Morphology to Atrial Fibrillation Recurrence After Radiofrequency Ablation - Gong, Shiyu; Zhou, Jian; Li, Bingyu; Kang, Sheng; Ma, Xiaoye; Cai, Ying; Guo, Yang; Hu, Rui; Zhang, Xumin (Frontiers in Cardiovascular Medicine, 2021)
Objective: The probability of late recurrent atrial fibrillation (AF) after radiofrequency ablation (RFA) has not yet been fully clarified. This study aims to study the association of left atrial appendage (LAA) morphology with AF recurrence after RFA. Methods: We retrospectively enrolled 84 patients (24 patients had persistent AF, 60 patients had paroxysmal AF) who underwent RFA in Shanghai East Hospital from June 2014 to May 2018. The mean follow-up of these patients was 618.6 days. According to preoperative transesophageal echocardiography (TEE), the morphology feature of LAA was classified and evaluated by two classification methods. The first method was divided into chicken-wing, windsock, cactus, and cauliflower, and the second method was divided into one lobe, two lobes, and multiple lobes. The correlation between morphological feature of LAA and the recurrence rate of AF after RFA was analyzed. Results: During follow-up, 12 patients (50%) and 10 patients (16.7%) had AF recurrence in persistent and paroxysmal AF, respectively. The LAA morphology was associated with the recurrence of AF after RFA with the chicken-wing highest recurrence risk (68.2%). The structure type of LAA was also related to the AF recurrence rate (p < 0.01). Compared with one lobe and multiple lobes, two lobes (recurrence, 47.6%) were more likely associated with the recurrence of AF (p < 0.02). Logistic regression analysis showed that the chicken-wing group had a higher risk of recurrence after RFA (OR = 8.13, p = 0.004), and the windsock group had a lower risk of recurrence (OR = 0.17, p = 0.002). Conclusion: The morphological feature of LAA is related to the recurrence risk of AF after RFA. LAA morphology assessment can predict the risk of AF recurrence.